2019
DOI: 10.1186/s41935-019-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and quantification of DNA from epithelial cells obtained from acrylic removable partial denture for sex identification

Abstract: Background: This study is aimed to evaluate the use of epithelial cells adhering the acrylic removable partial denture in establishing the sex of the individual using sex-determining region of the Y chromosome (SRY) gene. With a hypothesis that prosthetic appliance can also be used as a source of DNA in forensics for sex determination. A sample of 30 partial dentures from different denture wearers was selected for this study. Informed consent was taken from the subjects and institutional ethical clearance was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The results showed that most of the studies succeeded in DNA extraction except for two studies (Srivastava et al 2017;Chowdhury et al 2018). The sex identification was accurately defined in six studies (Zapico and Ubelaker 2013;Chauhan et al 2016;Kholief et al 2017;Dutta et al 2017;Bharath et al 2019), and in four studies, not all samples were identified correctly (Reddy et al 2011;Srivastava et al 2017;Chowdhury et al 2018;Lim et al 2019). The conclusion from ten studies was that teeth, mesiodens, dental pulp, and dentin are reliable sources for DNA with resistance to forensic insult unless subjected to extreme degradation and that also toothbrushes and dental prostheses were good DNA sources.…”
Section: Molecular Analysis For Sex Determination In Forensic Dentistmentioning
confidence: 96%
See 4 more Smart Citations
“…The results showed that most of the studies succeeded in DNA extraction except for two studies (Srivastava et al 2017;Chowdhury et al 2018). The sex identification was accurately defined in six studies (Zapico and Ubelaker 2013;Chauhan et al 2016;Kholief et al 2017;Dutta et al 2017;Bharath et al 2019), and in four studies, not all samples were identified correctly (Reddy et al 2011;Srivastava et al 2017;Chowdhury et al 2018;Lim et al 2019). The conclusion from ten studies was that teeth, mesiodens, dental pulp, and dentin are reliable sources for DNA with resistance to forensic insult unless subjected to extreme degradation and that also toothbrushes and dental prostheses were good DNA sources.…”
Section: Molecular Analysis For Sex Determination In Forensic Dentistmentioning
confidence: 96%
“…The conclusion from ten studies was that teeth, mesiodens, dental pulp, and dentin are reliable sources for DNA with resistance to forensic insult unless subjected to extreme degradation and that also toothbrushes and dental prostheses were good DNA sources. Amelogenin (Zapico and Ubelaker 2013;Nakanishi et al 2015;Chauhan et al 2016;Srivastava et al 2017;Dutta et al 2017;Chowdhury et al 2018;Lim et al 2019), SRY (Reddy et al 2011;Kholief et al 2017;Bharath et al 2019), and DYS14 (Kholief et al 2017) were all reliable in sex identification.…”
Section: Molecular Analysis For Sex Determination In Forensic Dentistmentioning
confidence: 97%
See 3 more Smart Citations